Slovenian public finances through the financial crisis - Verbič, Miroslav (Teorija in praksa, 2016)
In the article, we present the main Slovenian public finance aggregates and measures in times of the financial crisis. We describe the Slovenian macro - economic reality, starting positions in 2008, and the dynamics of macroeconomic aggregates in the crisis. We also present key public finance measures that were implemented to prevent the adverse influence of the crisis and simulations of their effects. The article is an attempt to summarise the consequences of the financial crisis in Slovenia, while it also presents some new results of simulations of the effects of the adopted measures to prevent the adverse influence of the crisis.
Keywords: 2008-2014; budgets; crises; Denarna kriza; finance; fiscal policy; fiskalna politika; Javne finance; krize; macroeconomics; makroekonomija; Monetary crisis; prevention; preventiva; proračuni; Public finance; savings; Slovenia; Slovenija; varčevanje